Análise microestrutural de nanopartículas de α-fe2-xcoxo3 (0≤x≤0.15) por difratometria de raios X - Raza, Adnan (2025)
In this study, the synthesis, structural characterization, and properties of crystalline nanoparticles of pure and cobalt-doped hematite with varying nominal concentrations [αFe₂₋ₓCoₓO₃ (x = 0.00, 0.05, 0.10, and 0.15)] were investigated. The nanoparticles were synthesized using the sol-gel method, which was chosen for its simplicity, low cost, and ability to produce high-quality nanoparticles with uniform composition. In this study, the optimization of the process was carried out with a focus on temperature. Structural and morphological analyses were performed using X-ray diffraction (XRD) and Rietveld refinement techniques. The XRD results revealed that all samples exhibited good crystallinity, with diffraction peaks corresponding to the rhombohedral structure (space group R3c). Non-linear shifts in diffraction peaks to lower angles were observed with increasing cobalt doping, indicating modifications in the lattice structure. The full width at half maximum (FWHM) and intensity showed greater fluctuation, while peak positions continuously shifted with doping. Rietveld refinement confirmed the formation of pure hematite (α-Fe₂O₃) in the undoped sample and a secondary cobalt ferrite (CoFe₂O₄) phase in the doped samples. The percentages of the secondary phase were 5.36%, 6.53%, and 8.32% for x = 0.05, 0.10, and 0.15, respectively, increasing with cobalt concentration. Structural analysis indicated significant shifts in lattice parameters and increased crystallite size with doping. Crystallite size values increased from 38.69 nm for pure hematite (x=0) to 60.24 nm, 46.67 nm, and 77.24 nm for cobalt doping concentrations of x = 0.05, 0.10 and 0.15, respectively. Density increased slightly with doping, from 5.373 g/cm³ (x=0.00) to 5.374 g/cm³ (x=0.15), due to cobalt atom substitution, while the unit cell volume decreased from 300.977 Å³ to 300.395 Å³. Lattice 6 parameter values for both phases decreased with higher dopant concentrations. The strain values were found to be 2.89%, 4.11%, 3.89%, and 3.28% for x = 0.00, 0.05, 0.10, and 0.15, respectively, highlighting the influence of cobalt on the crystal lattice. These findings demonstrate that cobalt doping significantly modifies the structural and morphological characteristics of hematite nanoparticles, offering insights into tailoring their properties for various technological applications.